Cerebral venous thrombosis and the use oral contraceptives: An integrative review (Research, Society and Development, 2021)
The aim of the study was to relate research on cerebral venous thrombosis with the use of combined oral contraceptives. This is an integrative literature review carried out using the following databases: LILACS, Scielo, Periódicos Capes, Medline PubMed, Cochrane Library and Science Direct, using the descriptors: "contraceptive agents", "intracranial embolism thrombosis", "thrombosis" "intracranial thrombosis". The Boolean operator "AND" was used between the descriptors to select the articles. The guiding question, elaborated through the PICO (Patient, Intervention, Control, Outcome) methodology, was: "Do oral contraceptives trigger cerebral venous thrombosis?". In the results, 47 articles were found, and 35 were excluded for not presenting a relationship between cerebral venous thrombosis and oral contraceptives. Thus, 12 articles were selected to compose this review. It can be concluded that the risk of venous thrombotic events in users of combined oral contraceptives is increased. Therefore, it is important to emphasize the rational use of these drugs, as well as the understanding for the early diagnosis of cerebral venous thrombosis.